Analysis of atomic-clock data to constrain variations of fundamental constants - Nathaniel Sherrill; Adam O Parsons; Charles F A Baynham; William Bowden; E Anne Curtis; Richard Hendricks; Ian R Hill; Richard Hobson; Helen S Margolis; Billy I Robertson; Marco Schioppo; Krzysztof Szymaniec; et al. (New Journal of Physics, 2023)
We present a new framework to study the time variation of fundamental constants in a model-independent way. Model independence implies more free parameters than assumed in previous studies. Using data from atomic clocks based on ^87 Sr, ^171 Yb ^+ and ^133 Cs, we set bounds on parameters controlling the variation of the fine-structure constant, α , and the electron-to-proton mass ratio, µ . We consider variations on timescales ranging from a minute to almost a day. In addition, we use our results to derive some of the tightest limits to date on the parameter space of models of ultralight dark matter and axion-like particles.